Karakterisasi Batubara untuk Underground Coal Gasification di Daerah Sekayu Musi Banyuasin - Eri Ilham Akbar; Dono Guntoro; Raden Maria Ulfa (Jurnal Riset Teknik Pertambangan, 2022)
Abstract. In determining the coal for UCG, several identifications are needed, including characterizing the coal, knowing the condition of the flanking rocks, and adjusting the parameters for the UCG itself. The research methodology carried out in this study started with a literature study in the form of secondary data such as regional geological maps, regional stratigraphy, previous investigations from the research area, and data on coal resources of the South Sumatra Basin in 2021. Then secondary data collection included lithology data, collar data, and data quality. The secondary data is then processed to produce coal chemical characteristics, log profiles, maps of the distribution of drill points and cross-section lines, and 3D stratigraphic models. Then the results of the data processing are adjusted to the UCG parameters. If these UCG parameters are met, the characteristics of the coal for UCG utilization are obtained. Based on the results of research that has been carried out the characteristics of the coal in the study area have a lignite rating with calorific values ranging from 4,197.80 – 4,949.00 kcal/kg (adb), water content 10.23 – 17.68% (adb), ash content 4, 23 – 16.25% (adb), volatile matter content 41.18 – 43.69% (adb), total sulfur 0.25 – 0.37% (adb), coal seam thickness 1.45 – 19.28 meters , with a layer depth of 3.43 – 98.00 meters. So that there is no coal seam in this study that can be developed for UCG because there is one parameter that is not achieved.Keywords: Coal, Underground Coal Gasification, UCG Parameters. Abstrak. Dalam penentuan batubara untuk UCG diperlukan beberapa identifikasi antara lain mengkarakterisasikan batubara, mengetahui kondisi batuan pengapit, dan menyesuaikan dengan parameter untuk UCG itu sendiri. Metodologi penelitian yang dilakukan pada penelitian ini dimulai dari studi literatur berupa data sekunder seperti peta geologi regional, stratigrafi regional, penyelidikan terdahulu dari daerah penelitian, dan data sumberdaya batubara cekungan Sumatera Selatan tahun 2021. Kemudian pengumpulan data sekunder meliputi data litologi, data collar, dan data quality. Data sekunder tersebut kemudian diolah untuk menghasilkan karakteristik kimia batubara, log profile, peta sebaran titik bor dan garis penampang, dan model stratigrafi 3D. Kemudian hasil pengolahan data tersebut disesuaikan dengan parameter UCG. Apabila parameter UCG ini terpenuhi maka didapatkan karakteristik batubara untuk pemanfaatan UCG ini. Berdasarkan hasil penelitian yang telah dilakukan karakteristik batubara daerah penelitian memiliki peringkat lignit dengan nilai kalori berkisar antara 4.197,80 – 4.949,00 kkal/kg (adb), kandungan air 10,23 – 17,68 % (adb), kandungan abu 4,23 – 16,25 % (adb), kandungan zat terbang 41,18 – 43,69 % (adb), total sulfur 0,25 – 0,37 % (adb), tebal lapisan batubara 1,45 – 19,28 meter, dengan kedalaman lapisan kedalaman 3,43 – 98,00 meter. Sehingga lapisan batubara pada penelitian ini tidak ada yang dapat dikembangkan untuk UCG karena terdapat salah satu parameter yang tidak tercapai.